High-voltage single-crystal positive electrode material coated with cobalt metaborate and preparation method and application of high-voltage single-crystal positive electrode material

By covered with boric acid cobalt in high -voltage single -crystal positive materials to form a lithium covering layer, the problem of complex process, poor structural stability and waste of resources in existing technologies, and realized high -efficiency and economical high -voltage positive positive materials preparation , Improve the performance and life of the battery.

CN119340362APending Publication Date: 2025-01-21SHAANXI IRICO NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411446771.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing high-voltage single-crystal positive electrode materials have complex preparation processes, poor structural stability, improper selection of dopants or coating agents leads to poor circulation and rate performance under high voltages, and high process requirements and waste resources.

Method used

A method for preparing high-voltage single crystal cathode materials coated with cobalt metaborate is adopted. A composite intermediate of cobalt metaborate and ternary single crystal material is generated on the ternary material matrix, and then combined with the ternary material to form a lithium cobalt metaborate coating layer. , using lower temperature to generate cobalt metaborate, simplifying the process and improving the controllability of reaction conditions.

Benefits of technology

It is achieved to simplify the process at low temperature, reduce the waste of resources, improve the multiplier performance, cycle performance, and high rate charging capacity of high voltage positive materials, extend the service life of the battery, and reduce the cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340362A_ABST
    Figure CN119340362A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt metaborate-coated high-voltage single-crystal positive electrode material and a preparation method and application thereof, and belongs to the technical field of lithium ion batteries, and the preparation method comprises the following steps: carrying out primary mixing and uniform dispersion on boric acid, a cobalt source and a first part of a ternary single-crystal positive electrode material, and carrying out primary sintering to obtain a cobalt metaborate and ternary single-crystal material composite intermediate; and carrying out secondary mixing with a second part of the ternary single-crystal positive electrode material, uniformly dispersing, and carrying out secondary sintering and crushing to obtain the cobalt metaborate-coated high-voltage single-crystal positive electrode material. The ternary single crystal positive electrode material is LiX (Ni Co Mn < c >) O < 2 >; wherein x is not less than 1.0 and not more than 1.2, a is not less than 0.5 and not more than 0.95, and a + b + c = 1. The intermediate is firstly generated on the ternary material substrate at low temperature, and then the intermediate and the ternary material form the cobalt lithium metaborate coating layer, so that the migration rate of the lithium ion battery in a high-voltage charging and discharging process is effectively promoted, the specific discharge capacity, the cycle capacity and the high-rate charging capacity of the battery at high voltage are improved, the preparation is simple, the reaction is easy to control, and the preparation cost is low. The industrial production conditions are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a high-voltage positive electrode material coated with cobalt metaborate, and a preparation method and application thereof. Background Art

[0002] As the sales of new energy vehicles continue to rise, higher and higher requirements are placed on the energy density of power batteries. At present, the industry mainly improves the energy density of ternary positive electrode materials by increasing the upper limit of charging voltage (high voltage) and increasing the nickel content (high nickel content). The proportion of high-nickel series ternary materials has gradually increased, and ultra-high nickel has further improved the competitiveness of high-nickel ternary materials. The high nickelization of ternary positive electrode materials refers to increasing the content of nickel in ternary materials, thereby increasing energy density and correspondingly reducing dependence on cobalt. With the rise of the medium nickel voltage platform, the energy density performance of the high-voltage line tends to be consistent with the high-nickel ternary structure. The high-voltage route increases the stop voltage of the positive electrode material battery charging, thereby removing more lithium ions at a higher voltage, thereby increasing the capacity and operating voltage at the same time, thereby achieving the purpose of increasing energy density. In the high-voltage direction, although the high-voltage ternary positive electrode material can effectively improve the energy density of the material, it faces a series of challenges such as crystal structure stability, phase change, interface side reactions and oxygen release in the application of voltages of 4.4V and above, making the development of the material have extremely high technical barriers.

[0003] At present, doping and surface modification technology are mainly used to reduce the free lithium of the product, reduce the DC internal resistance, and improve the cycle stability of single crystal ternary materials under high temperature, high nickel, and high pressure environments. However, improper selection of dopants or coating agents will result in poor cycle and rate performance under high voltage, so it is particularly important to choose a suitable dopant or coating agent. Chinese patent application CN111200120B discloses a method of mixing a boron source with a cobalt source, sintering at 400-600°C in a protective atmosphere to obtain cobalt borate, and then mixing and sintering with ternary materials to obtain a finished product. The residual alkali content of the ternary positive electrode material can be reduced to a certain extent, and the rate discharge capacity and cycle performance can be improved, but the entire process requires a high temperature, which wastes resources in actual industrial production.

[0004] In view of the problems of complex process, poor structural stability under high voltage conditions, improper selection of dopants or coating agents leading to poor cycle and rate performance under high voltage, poor cycle performance, high process requirements and waste of resources in the current high-voltage single crystal positive electrode material preparation process, it is urgent to develop a simple method for preparing high-voltage single crystal positive electrode materials with better rate performance and cycle performance, and high nickel ternary positive electrode materials that can solve the residual alkali problem are of great significance to this field. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high-voltage positive electrode material coated with cobalt metaborate and a preparation method and application thereof, so as to solve the technical problems of complex process, poor structural stability and poor cycle performance under high voltage conditions in the current high-voltage single crystal positive electrode material preparation process.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention discloses a method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising: mixing boric acid, a cobalt source and a first portion of a ternary single crystal positive electrode material, dispersing them uniformly, and sintering them once to obtain a composite intermediate of cobalt metaborate and the ternary single crystal material; and then mixing the composite intermediate of cobalt metaborate and the ternary single crystal material and a second portion of the ternary single crystal positive electrode material for a second time, dispersing them uniformly, sintering them for a second time, and crushing them to obtain the high-voltage single crystal positive electrode material coated with cobalt metaborate;

[0008] The ternary single crystal positive electrode material is Li X (Ni a Co b Mn c ) 2 ;

[0009] Among them, 1.0≤x≤1.2, 0.5≤a≤0.95, a+b+c=1.

[0010] Preferably, the cobalt source is any one or more of cobalt hydroxide and cobalt oxide.

[0011] Preferably, the molar ratio of boric acid, cobalt source and the first portion of ternary single crystal positive electrode material is (3-6): (1-4): (1-6).

[0012] Preferably, the mixing method of the one-time mixing is any one of a ball mill mixer, a drum mixer, a high-speed mixer, a cone mixer, a ribbon mixer and a plowshare mixer.

[0013] Preferably, the conditions for the primary sintering are: a sintering temperature of 200 to 500° C., a heat preservation time of 2 to 10 hours, and a heating rate of 1 to 8° C. / min.

[0014] Preferably, the mass ratio of the cobalt metaborate and the ternary single crystal material composite intermediate to the second ternary single crystal positive electrode material is (0.05% to 0.30%):1.

[0015] Preferably, the secondary mixing is carried out by any one of a ball mill mixer, a drum mixer, a high-speed mixer, a cone mixer, a ribbon mixer and a plowshare mixer.

[0016] Preferably, the conditions for the secondary sintering are: a sintering temperature of 250 to 700° C., a holding time of 6 to 15 hours, and a heating rate of 1 to 8° C. / min.

[0017] The invention also discloses a high-voltage single crystal positive electrode material coated with cobalt metaborate, which is prepared by the above preparation method.

[0018] The invention also discloses the application of the high-voltage single crystal positive electrode material coated with cobalt metaborate prepared by the preparation method in a lithium ion battery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention discloses a method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate. At low temperature, a composite intermediate of cobalt metaborate and ternary single crystal material is generated on a ternary material substrate, and then the composite intermediate of cobalt metaborate and ternary single crystal material is reacted with the ternary material to form a cobalt metaborate lithium coating layer. The cobalt metaborate is generated at a relatively low temperature, which can save costs to a certain extent, and the manufacturing process is simple, the reaction conditions are easy to control, the repeatability is good, and it has good application prospects. The use of cobalt metaborate as a coating material can reduce residual lithium hydroxide and lithium carbonate, thereby reducing the amount of residual alkali. Cobalt metaborate is used as a coating material to form a cobalt metaborate lithium coating layer with the ternary material, which can effectively promote the migration rate of lithium-ion batteries during high-voltage charging and discharging, improve the battery's discharge specific capacity, cycle capacity and high-rate charging capacity, and meet industrial production conditions at the same time.

[0021] The present invention also discloses a high-voltage single crystal positive electrode material coated with cobalt metaborate prepared by the above-mentioned preparation method. The high-voltage single crystal positive electrode material coated with cobalt metaborate exhibits excellent performance, and its 0.1C first efficiency%, that is, the efficiency of (0.1C discharge / 0.1C charge), is 88.46%-89.16%, showing efficient initial charge and discharge capability; rate performance%, that is, the discharge and charge efficiency (1C / 0.2C), is 87.58%-87.89%, indicating that the material can maintain stable performance at different charge and discharge rates; cycle performance%, that is, (1C 100 cycle capacity retention rate), is 71.53%-77.82%, proving that the material has excellent capacity retention capability during long-term use.

[0022] The present invention also discloses the application of the high-voltage single crystal positive electrode material coated with cobalt metaborate obtained by the above-mentioned preparation method in lithium-ion batteries, which can significantly improve the discharge specific capacity of the battery, so that the battery can store more energy, thereby meeting the demand for high endurance, which is of great significance for application fields such as new energy vehicles. At the same time, the positive electrode material can also significantly improve the cycle capacity of the battery, extend the service life of the battery, reduce the cost of use, and improve the economy of the battery. In addition, it can also enhance the high-rate charging capacity of the battery, achieve fast charging, and improve the user's convenience. It can meet the conditions of industrial production, and is expected to provide new solutions for improving the performance of lithium-ion batteries and reducing costs, promote the further development of the lithium-ion battery industry, and contribute to the popularization and sustainable development of clean energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a SEM image of a high-voltage single crystal positive electrode material coated with cobalt metaborate disclosed in Example 1 of the present invention;

[0024] Figure 2 This is a schematic diagram of a method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate disclosed in the present invention. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0026] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0027] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0028] See also Figure 1This is a SEM image of a high-voltage single crystal positive electrode material coated with cobalt metaborate disclosed in Example 1 of the present invention; it can be seen from the figure that the surface coating layer of the high-voltage single crystal positive electrode material coated with cobalt metaborate prepared in Example 1 is thin and uniform, which can prove that it was successfully prepared and has good uniformity. These characteristics give the positive electrode material excellent electrochemical performance and broad application prospects.

[0029] See also Figure 2 The present invention discloses a method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate; as can be seen from the figure, the method for preparing the high-voltage single crystal positive electrode material coated with cobalt metaborate comprises: mixing boric acid, a cobalt source and a first portion of a ternary single crystal positive electrode material, dispersing them uniformly, and sintering them once to obtain a composite intermediate of cobalt metaborate and ternary single crystal material; and then mixing the composite intermediate of cobalt metaborate and ternary single crystal material with a second portion of a ternary single crystal positive electrode material for a second time, dispersing them uniformly, sintering them twice, and crushing them to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate. The present invention first generates a composite intermediate of cobalt metaborate and ternary single crystal material on a ternary material substrate at low temperature, and then forms a cobalt metaborate lithium coating layer with the ternary material, which effectively promotes the migration rate of lithium-ion batteries in the high-voltage charge and discharge process, improves the discharge specific capacity, cycle and high-rate charging capacity of the battery under high voltage, and has a simple manufacturing process, easy-to-control reaction conditions, and meets industrial production conditions.

[0030] The present invention discloses a method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0031] Step 1: Boric acid, cobalt source and ternary single crystal cathode material Li X (Ni a Co b Mn c ) 2 The mixture is uniformly dispersed in a certain mixing manner according to a certain proportion, and then placed in a muffle furnace and sintered under specific conditions to obtain a composite intermediate of cobalt metaborate and ternary single crystal material, wherein 1.0≤x≤1.2, 0.5≤a≤0.95, and a+b+c=1;

[0032] Specifically, the cobalt source includes one or more of cobalt hydroxide and cobalt oxide.

[0033] Specifically, the specific ratio is that the molar ratio of boric acid, cobalt source and ternary single crystal positive electrode material is (3-6): (1-4): (1-6).

[0034] Specifically, the specific sintering conditions are: a sintering temperature of 200 to 500° C., a holding time of 2 to 10 hours, and a heating rate of 1 to 8° C. / min.

[0035] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li X (Ni a Co b Mn c ) 2 The materials are uniformly dispersed in a certain mixing method according to a specific ratio, and then the mixture is placed in a muffle furnace and sintered under specific conditions to obtain a ternary positive electrode material coated with cobalt metaborate.

[0036] Specifically, the weight ratio of the cobalt metaborate and the ternary single crystal material composite intermediate to the ternary single crystal positive electrode material is controlled at 0.05% to 0.30%.

[0037] Specifically, the mixing method includes one of a ball mill mixer, a drum mixer, a high-speed mixer, a cone mixer, a ribbon mixer and a plowshare mixer, and is determined according to the actual mixing weight.

[0038] Specifically, the specific sintering conditions are: a sintering temperature of 250 to 700° C., a holding time of 6 to 15 hours, and a heating rate of 1 to 8° C. / min.

[0039] Step 3: The obtained cobalt borate-coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material.

[0040] The present invention also discloses a high-voltage single crystal positive electrode material coated with cobalt metaborate prepared by the above-mentioned preparation method, wherein the 0.1C first efficiency%, i.e., the efficiency of (0.1C discharge / 0.1C charge), is 88.46%-89.16%, showing a high-efficiency initial charge and discharge capability; the rate performance%, i.e., the discharge and charge efficiency (1C / 0.2C), is 87.58%-87.89%, indicating that the material can maintain stable performance at different charge and discharge rates; the cycle performance%, i.e., (1C 100 cycle capacity retention rate), is 71.53%-77.82%, proving that the material has excellent capacity retention capability during long-term use.

[0041] The high-voltage single crystal positive electrode material coated with cobalt metaborate can form a protective film on the surface of the ternary single crystal positive electrode material by coating with cobalt metaborate, effectively isolating the direct contact between the positive electrode material and the electrolyte, reducing the occurrence of interface side reactions, and thus improving the crystal structure stability of the material. The introduction of cobalt metaborate can also improve the thermal stability of the positive electrode material, so that it can still maintain good electrochemical performance under high temperature environment. This is of great significance for improving the safety and cycle life of the battery. Since the ternary single crystal positive electrode material itself has a high energy density, its crystal structure can be further optimized after coating with cobalt metaborate, thereby further improving the energy density. This is of great significance for meeting the demand for high energy density batteries in fields such as new energy vehicles. The coating layer can effectively reduce the volume expansion and contraction of the positive electrode material during the charging and discharging process, reduce the risk of material pulverization, and thus improve the cycle stability of the battery. This is of great significance for extending the service life of the battery. The coating layer also helps to improve the ionic conductivity of the positive electrode material and reduce the charge transfer resistance, thereby improving the rate performance of the battery. This means that the battery can be charged and discharged at a higher rate to meet the needs of fast charging and discharging.

[0042] The present invention also discloses the application of the high-voltage single crystal positive electrode material coated with cobalt metaborate prepared by the above-mentioned preparation method in a lithium-ion battery. The cobalt metaborate coating layer can effectively isolate the direct contact between the positive electrode material and the electrolyte, reduce the occurrence of interface side reactions, and thus protect the crystal structure of the positive electrode material from being destroyed during the cycle. This significantly prolongs the cycle life of the battery and improves the economic efficiency of the battery. The single crystal positive electrode material itself has good mechanical strength, and the coating layer further enhances its ability to resist volume changes. During the charge and discharge process, the positive electrode material will undergo a certain degree of volume expansion and contraction, and the coating layer can effectively buffer these changes and prevent the material from pulverizing and falling off. The cobalt metaborate coating layer has high thermal stability and can maintain structural integrity under high temperature conditions, thereby preventing the battery from thermal runaway or explosion due to overheating and other safety accidents. This is of great significance for improving the overall safety of the battery. The cobalt metaborate coating layer has excellent ion transport performance, which can accelerate the embedding and extraction process of lithium ions in the positive electrode material, thereby improving the charge and discharge rate of the battery. This enables the battery to charge and discharge quickly in a short period of time, meeting the needs of high power output or fast charging. With the increasing demand for high energy density and long cycle life batteries in new energy vehicles, portable electronic devices and other fields, high voltage single crystal cathode materials coated with cobalt metaborate have broad application prospects. This material can not only meet the application requirements under high voltage conditions, but also improve the overall performance and service life of the battery, providing strong support for the development of related fields.

[0043] Example 1

[0044] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0045] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 3:4:3, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 200°C at 5°C / min, and kept warm for 3 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0046] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.05%, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 500°C at 5°C / min, and kept warm for 6 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0047] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0048] Example 2

[0049] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0050] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 3:4:3, and the mixing method is a drum mixer. The mixture is then placed in a muffle furnace, heated to 500°C at 5°C / min, and kept warm for 10 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0051] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2The mixture is uniformly dispersed at a weight ratio of 0.30%, and the mixing method is a drum mixer. The mixture is then placed in a muffle furnace, heated to 700°C at a rate of 5°C / min, and kept warm for 15 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0052] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0053] Example 3

[0054] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0055] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 3:4:3, and the mixing method is a high-speed mixer. The mixture is then placed in a muffle furnace, heated to 350°C at 5°C / min, and kept warm for 6 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0056] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.15%, and the mixing method is a high-speed mixer. The mixture is then placed in a muffle furnace, heated to 500°C at a rate of 5°C / min, and kept warm for 10 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0057] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0058] Example 4

[0059] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0060] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2The mixture is evenly dispersed in a molar ratio of 6:1:1, and the mixing method is a conical mixer. The mixture is then placed in a muffle furnace, heated to 350°C at 5°C / min, and kept warm for 6 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0061] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.15%, and the mixing method is a conical mixer. The mixture is then placed in a muffle furnace, heated to 500°C at 5°C / min, and kept warm for 10 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0062] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0063] Example 5

[0064] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0065] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 6:4:1, and the mixing method is a ribbon mixer. The mixture is then placed in a muffle furnace, heated to 350°C at a rate of 5°C / min, and kept warm for 6 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0066] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.15%, and the mixing method is a ribbon mixer. The mixture is then placed in a muffle furnace, heated to 500°C at a rate of 5°C / min, and kept warm for 10 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0067] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0068] Example 6

[0069] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0070] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 3:2:3, and the mixing method is a plowshare mixer. The mixture is then placed in a muffle furnace, heated to 350°C at a rate of 5°C / min, and kept warm for 6 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0071] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.15%, and the mixing method is a plowshare mixer. The mixture is then placed in a muffle furnace, heated to 500°C at a rate of 5°C / min, and kept warm for 10 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0072] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0073] Example 7

[0074] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0075] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are mixed with Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 3:4:6, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 350°C at 5°C / min, and kept warm for 6 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0076] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2The mixture is uniformly dispersed at a weight ratio of 0.15%, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 500°C at 5°C / min, and kept warm for 10 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0077] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0078] Example 8

[0079] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0080] Step 1: Boric acid, cobalt oxide and ternary single crystal cathode material are mixed with Li 1.0 (Ni 0.5 Co 0.2 Mn 0.3 ) 2 The mixture is evenly dispersed in a molar ratio of 4:3:4, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 400°C at 8°C / min, and kept warm for 2 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0081] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.0 (Ni 0.5 Co 0.2 Mn 0.3 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.2%, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 250°C at a rate of 1°C / min, and kept warm for 15 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0082] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0083] Example 9

[0084] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0085] Step 1: Boric acid, cobalt hydroxide and ternary single crystal cathode material are reacted with Li 1.2 (Ni 0.95 Co 0.01 Mn 0.04 ) 2The mixture is evenly dispersed in a molar ratio of 5:4:5, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 200°C at a rate of 1°C / min, and kept warm for 10 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0086] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.2 (Ni 0.95 Co 0.01 Mn 0.04 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.25%, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 400°C at 8°C / min, and kept warm for 12 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0087] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0088] Example 10

[0089] A method for preparing a high-voltage single crystal positive electrode material coated with cobalt metaborate, comprising the following steps:

[0090] Step 1: Boric acid, cobalt hydroxide, cobalt oxide and ternary single crystal cathode material are mixed with Li 1.1 (Ni 0.7 Co 0.15 Mn 0.15 ) 2 The mixture is evenly dispersed in a molar ratio of 3:4:3, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 200°C at 3°C / min, and kept warm for 4 hours. After sintering, a composite intermediate of cobalt metaborate and ternary single crystal material can be obtained.

[0091] Step 2: Compound the obtained cobalt borate with the ternary single crystal material intermediate and the ternary single crystal positive electrode material Li 1.1 (Ni 0.7 Co 0.15 Mn 0.15 ) 2 The mixture is uniformly dispersed at a weight ratio of 0.3%, and the mixing method is a ball mill mixer. The mixture is then placed in a muffle furnace, heated to 600°C at 3°C / min, and kept warm for 8 hours to obtain a ternary positive electrode material coated with cobalt metaborate;

[0092] Step 3: The obtained cobalt metaborate coated ternary positive electrode material is crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate.

[0093] Comparative Example 1

[0094] A method for preparing a high voltage single crystal positive electrode material comprises the following steps:

[0095] Step 1: Ternary single crystal cathode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 Place it in a muffle furnace, heat it to 500°C at 5°C / min, and keep it warm for 10 hours to obtain the ternary positive electrode material;

[0096] Step 2: The obtained ternary positive electrode material is crushed to obtain a high voltage single crystal positive electrode material.

[0097] Comparative Example 2

[0098] A method for preparing a high voltage single crystal positive electrode material comprises the following steps:

[0099] Step 1: Ternary single crystal cathode material Li 1.04 (Ni 0.6 Co 0.1 Mn 0.3 ) 2 Place it in a muffle furnace, heat it to 700°C at 5°C / min, and keep it warm for 15 hours to obtain the ternary positive electrode material;

[0100] Step 2: The obtained ternary positive electrode material is crushed to obtain a high voltage single crystal positive electrode material.

[0101] The samples of the above embodiments and the comparative examples were respectively mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 95:3:2 and N-methylpyrrolidone was added to prepare slurries. The 2025 type button battery production test was carried out, and the rate charge and discharge test was carried out in the voltage range of 3.0V to 4.7V, wherein the rate performance test conditions were: 0.1C, 0.2C, 0.5C and 1C.

[0102] See Table 1 for the electrochemical properties of samples prepared in Examples 1-10 of the present invention and samples prepared in Comparative Examples 1 and 2; it can be seen from the table that the first efficiency and cycle of the samples are improved after cobalt borate coating, and the rate performance is not significantly different from that of the comparative samples.

[0103] Table 1 Electrochemical properties of samples prepared in Examples 1-7 and samples prepared in Comparative Examples 1 and 2

[0104]

[0105] The advantages of a high-voltage single crystal positive electrode material coated with cobalt metaborate disclosed in the present invention include:

[0106] 1. The present invention uses cobalt metaborate as the coating material, which can reduce the residual lithium hydroxide and lithium carbonate, thereby reducing the residual alkali amount.

[0107] 2. Cobalt borate is used as a coating material to form a cobalt borate lithium coating layer with the ternary material, which can effectively promote the migration rate of lithium-ion batteries during high-voltage charging and discharging, and improve the battery's discharge capacity, cycle capacity and high-rate charging capacity.

[0108] 3. The present invention utilizes a relatively low temperature to generate cobalt metaborate, which can save costs to a certain extent, and has a simple manufacturing process, easily controllable reaction conditions, good repeatability, and good application prospects.

[0109] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate, characterized in that: include: The boric acid, the cobalt source and the first portion of the ternary single crystal positive electrode material are mixed once, dispersed evenly, and sintered once to obtain a composite intermediate of cobalt metaborate and the ternary single crystal material; the cobalt metaborate and the ternary single crystal material composite intermediate and the second portion of the ternary single crystal positive electrode material are mixed again, dispersed evenly, sintered twice, and crushed to obtain a high-voltage single crystal positive electrode material coated with cobalt metaborate; The ternary single crystal positive electrode material is Li X (Ni a Co b Mn c )O2; Among them, 1.0≤x≤1.2, 0.5≤a≤0.95, a+b+c=1.

2. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The cobalt source is any one or more of cobalt hydroxide and cobalt oxide.

3. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The molar ratio of the boric acid, the cobalt source and the first portion of the ternary single crystal positive electrode material is (3-6): (1-4): (1-6).

4. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The mixing method of the primary mixing is any one of a ball mill mixer, a drum mixer, a high-speed mixer, a cone mixer, a ribbon mixer and a plowshare mixer.

5. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The conditions of the primary sintering are: sintering temperature is 200-500° C., holding time is 2-10 hours, and heating rate is 1-8° C. / min.

6. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The mass ratio of the cobalt metaborate and ternary single crystal material composite intermediate to the second ternary single crystal positive electrode material is (0.05% to 0.30%):

1.

7. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The secondary mixing is carried out in any one of a ball mill mixer, a drum mixer, a high-speed mixer, a cone mixer, a ribbon mixer and a plowshare mixer.

8. The method for preparing a high voltage single crystal positive electrode material coated with cobalt metaborate according to claim 1, characterized in that: The conditions of the secondary sintering are: sintering temperature is 250-700° C., holding time is 6-15 hours, and heating rate is 1-8° C. / min.

9. A high voltage single crystal positive electrode material coated with cobalt metaborate, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the high-voltage single crystal positive electrode material coated with cobalt metaborate obtained by the preparation method according to any one of claims 1 to 8 in lithium-ion batteries.

Citation Information

Patent Citations

  • A ternary cathode material, its preparation method, and a lithium-ion battery

    CN111200120B